Effective derivative hedging and initial public offering long‐run performance. (17th July 2013) - Nguyen, Hoa; Liu, Ming‐Hua; Gallagher, David
Abstract We investigate the role of corporate currency risk management through the use of financial derivatives in influencing the long‐run performance of a sample of Australian resources companies. We find that derivative users generally outperformed nonderivative users in the 5‐year period following listing. Effective derivative users consistently outperformed the nonhedgers. Furthermore, within the population of derivative users, effective derivative users tended to perform better than ineffective hedgers. Our results indicate that effective financial risk management plays a role in long‐run IPO performance.